PENGARUH PENERAPAN ELEKTRONIK SURAT PEMBERITAHUAN (E-SPT) DAN PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DI KPP PRATAMA PROVINSI BENGKULU - Intan Sri Hari Cahyani; Subaeti Subaeti (Universitas Prof.Hazairin,SH Bengkulu, 2019)
This study aims to determine the effect of the application of electronic notification (E-spot) and knowledge of taxation on taxpayer compliance in the KPP Pratama Bengkulu Province by using the data analysis, namely validity test, reliability test, normality test, multiple regression, partial t-test, test f-simultaneous and determination. From the calculation results obtained by the regression equation Y = 4,621 + 0,013 + 0,752 + e, with the value of the coefficient of determination (R Square) of 0,468 this shows that jointly the electronic application variable notification letter (E-Spt) and taxation knowledge of 46.8% while the remaining 53.2% is influenced by other variables not included in this study. Based on the results of the simultaneous testing shows that the electronic variable notification letter (X1) and knowledge taxation variable (X2) have a significant influence jointly towards Taxpayer Compliance (Y) with a value of fcount> ftabel = 11, 899> 3.35 then Ha is accepted Ho is rejected.